Primary Phagocytosis of Neurons by Inflamed Microglia: Potential Roles in Neurodegeneration - Neher, Jonas J.; Neniskyte, Urte; Brown, Guy C. (Frontiers in Pharmacology, 2012)
Microglial phagocytosis of dead or dying neurons can be beneficial by preventing secondary necrosis and release of pro-inflammatory intracellular components. However, there is now evidence that under certain conditions microglia can also phagocytose viable neurons, thus executing their death. In particular, microglia eliminate synapses and neurons during development, but they also kill neurons through phagocytosis during neuroinflammation in the mature brain. Neuroinflammation accompanies many neurodegenerative diseases, such as Alzheimer’s Disease, Parkinson’s Disease, Frontotemporal Dementia and Multiple Sclerosis. In this review, we discuss the evidence supporting a role for primary phagocytosis in neurodegeneration and outline the mechanisms of this process.